2008
DOI: 10.1111/j.1468-3156.2008.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

Resisting having learning disabilities by managing relative abilities

Abstract: Accessible summary People who attended a community centre for people with learning disabilities talked to researchers about the centre, their school and personal experiences. The researchers were interested in what the people in the study said about learning disabilities. This study found that people who attended the centre compared their abilities to those of others around them to make sense of who they are. People in the study presented themselves positively by describing their abilities in comparison to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 17 publications
2
21
0
Order By: Relevance
“…Therefore, Freddie explicitly positions himself as ‘we’, a service‐user who speaks his mind, in contrast to ‘other’ service‐users with learning disabilities, who do not. This is similar to previous reports of people who have been labeled grouping others who use similar services as a less able ‘them’, leaving the self in a more able ‘us’ category (Bogdan & Taylor, 1994; Davies & Jenkins, 1997; Finlay & Lyons, 2000, 2005; McVittie, Goodall, & McKinlay, 2008). The conversation continues in the following extract.…”
Section: Methodssupporting
confidence: 88%
See 2 more Smart Citations
“…Therefore, Freddie explicitly positions himself as ‘we’, a service‐user who speaks his mind, in contrast to ‘other’ service‐users with learning disabilities, who do not. This is similar to previous reports of people who have been labeled grouping others who use similar services as a less able ‘them’, leaving the self in a more able ‘us’ category (Bogdan & Taylor, 1994; Davies & Jenkins, 1997; Finlay & Lyons, 2000, 2005; McVittie, Goodall, & McKinlay, 2008). The conversation continues in the following extract.…”
Section: Methodssupporting
confidence: 88%
“…An identity construction of competence in contrast to other residents was produced by Freddie to complain about staff restrictions on his behaviour. As McVittie et al . (2008) argue, constructions of relative abilities are used to do discursive work – here to build complaints.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This approach includes controversial practices such as cochlear implants to enable sound perception in deaf children (Tucker, 1998) or plastic surgery to alter characteristic facial features of children with Down syndrome (Arndt, Lefebvre, Travis, & Munro, 1986;Olbrisch, 1985). Alternatively, one may strive to overcome disabilities by compensating or ''trying harder'' in the face of obstacles, rejecting accommodations and striving to meet normative standards of achievement (McVittie, Goodall, & McKinlay, 2008;Phillips, 1985). The emphasis across these strategies is individual mobility, grounded in the assumption that a person can improve self-esteem by minimizing their impairments and approaching, to the degree possible, broader societal norms of functioning (Charmaz, 1995).…”
Section: Coping With Disability Stigma: Individualistic and Collectivmentioning
confidence: 98%
“…First, it has been suggested that label ID is central or salient to researchers examining the area of identity and self, and that many researchers have failed to consider the alternative identities that might be more important and meaningful to people with an ID beyond that imposed on them by society (McVittie, Goodall, and McKinlay 2008). The importance assigned to the social category of intellectual disability is also reflected in the paucity of literature examining the alternative identities that people with an intellectual disability may embody, including gendered and ethnic identities (McVittie, Goodall, andMcKinlay 2008, Block, Balcazar, andKeys 2001). Second, by focusing on whether a person with an intellectual disability is aware or unaware of this label, researchers are failing to recognise that identity is negotiable (McVittie, Goodall, andMcKinlay 2008, Rapley 2004).…”
Section: Introductionmentioning
confidence: 99%